Cautionary tales : a collection of scary stories starring favorite Disney villains! - Pearson, Ridley (Disney Press, 2022)
A collection of illustrated Disney stories--including Snow White and Aladdin--retold as cautionary, scary, unsettling stories, which Billie Templeton and her classmate, Tim, fall into after Tim finds and ignores the warnings about a magic mirror. Not following the rules, they will find, has a huge cost.